2009
DOI: 10.1007/s00520-009-0793-1
|View full text |Cite
|
Sign up to set email alerts
|

Living with multiple myeloma: experiences of patients and their informal caregivers

Abstract: While health professionals' attention has been concentrated in helping patients to get through treatments, it is imperative that psychosocial rehabilitation is offered also to those who survive many years after diagnosis and are off treatments. Caregivers are particularly vulnerable to the high demands of caring for myeloma patients, and a more concerted action by health professionals should be directed to them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
112
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(121 citation statements)
references
References 26 publications
3
112
1
5
Order By: Relevance
“…The use of CAM in cancer patients has increased over the last few decades 23,24 . Yildirim It is fairly predictable that as the symptom experience intensifies that the quality of life for these women will deteriorate over time [27][28][29][30] . Eventually the resources at the women's disposal will be insufficient to the challenge of the wound and the other problems they face.…”
Section: Discussionmentioning
confidence: 99%
“…The use of CAM in cancer patients has increased over the last few decades 23,24 . Yildirim It is fairly predictable that as the symptom experience intensifies that the quality of life for these women will deteriorate over time [27][28][29][30] . Eventually the resources at the women's disposal will be insufficient to the challenge of the wound and the other problems they face.…”
Section: Discussionmentioning
confidence: 99%
“…Family caregivers become responsible for many elements of cancer care, such as scheduling visits, providing accommodation, monitoring treatment compliance, symptom management, emotional support, meal preparation, housekeeping, and providing financial support (Given et al, 2001;Stenberg et al, 2010), but this usually occurs with insufficient preparation or training in the provision of care. Caregivers often neglect their own needs, and are even often required to give up their usual daily activities due to their caregiving responsibilities (Beesley et al, 2011;Molassiotis et al, 2011). These efforts to care for their loved ones burden family caregivers.…”
Section: Introductionmentioning
confidence: 98%
“…Psychologically, high levels of depression were found in myeloma patients, with a direct relationship between unmet needs and both depression and anxiety (Molassiotis et al, 2011b). Qualitative studies investigating patients' experience with myeloma have similarly revealed that patients living with myeloma face a multitude of physical (Kelly and Dowling, 2011;Molassiotis et al, 2011a;Potrata et al, 2011) and emotional factors (Kelly and Dowling, 2011;Molassiotis et al, 2011a), while the impact of living with an 'unknown future' was the only theme that was explicitly reported within all the studies (Kelly and Dowling, 2011;Molassiotis et al, 2011a;Potrata et al, 2011). While these studies provide valuable insight into the quality of life and experience of myeloma, they typically involve older patients, as myeloma is a disease more prevalent in the older age ranges.…”
Section: Introductionmentioning
confidence: 93%
“…Existing research suggests that, among people with haematological malignancies, patients with myeloma have the lowest quality of life and highest level of symptoms due to the added distress of bone pain, pathological fractures and recurrent infections (Johnsen et al, 2009). Studies specifically investigating the experiences (Kelly and Dowling, 2011;Molassiotis et al, 2011a;Potrata et al, 2011) and quality of life (Molassiotis et al, 2011b;Mols et al, 2012) of patients living with myeloma reveal low performance on health-related quality of life (HRQOL) sub-scales, including global quality of life, physical functioning, role functioning, and social and cognitive functioning. Psychologically, high levels of depression were found in myeloma patients, with a direct relationship between unmet needs and both depression and anxiety (Molassiotis et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%